EFFICACY OF PAIN MANAGEMENT AT PREHOSPITAL STAGE IN CHILDREN WITH SEVERE THERMAL TRAUMA - D. K. Azovskiy; A. U. Lekmanov; L. I. Budkevich; S. F. Pilutik; D. S. Gudilov (Вестник анестезиологии и реаниматологии, 2018)
To describe the frequency and type of EMS analgesic administration to burned children; to describe pain after PICU admission used specific score FLACC and Wong-Baker FACES factors associated with the administration of analgesia by EMS. This was a retrospective study of children (age < 18 years) who were transported by EMS between January 2013 and December 2014 and had a final hospital diagnosis of major burns (20% and more). Receipt of and time of parenteral analgesia were recorded and statistical studied. 232 children met the inclusion criteria. The mean (range) age of this sample was 3.7 (0.1-17) years. Only 201 patients received prehospital analgesia (87%). Opioids received analgesia in the EMS (53.23%). Tramadol received analgesia in the EMS (83.36%). Non-opioids received (nurofen, ketorol) analgesia in the EMS (65.28%). On painful scores, prehospital opioids analgesia was associated with no pain or little bit pain (2.11 ± 1.13), tramadol was associated with banging pain (5.84 ± 1.2), non-opioids group and group without analgesia was associated with really hurts (8.55 ± 0.92 and 8.83 ± 0.69). Statistically significant association was between opioids analgesia group and tramadol, non-opioids and group without analgesia (p ≤ 0.01). The need for strict guidelines for administration of opioids in children with severe burn injury, which ensures an adequate level of analgesia. Parenteral Tramadol can ensure only partial removal of pain. Unacceptable use of only non-narcotic analgesics or start transportation to hospital without analgesia. Key words: burns, pediatric, pain, prehospital.>< 18 years) who were transported by EMS between January 2013 and December 2014 and had a final hospital diagnosis of major burns (20% and more). Receipt of and time of parenteral analgesia were recorded and statistical studied. 232 children met the inclusion criteria. The mean (range) age of this sample was 3.7 (0.1-17) years. Only 201 patients received prehospital analgesia (87%). Opioids received analgesia in the EMS (53.23%). Tramadol received analgesia in the EMS (83.36%). Non-opioids received (nurofen, ketorol) analgesia in the EMS (65.28%). On painful scores, prehospital opioids analgesia was associated with no pain or little bit pain (2.11 ± 1.13), tramadol was associated with banging pain (5.84 ± 1.2), non-opioids group and group without analgesia was associated with really hurts (8.55 ± 0.92 and 8.83 ± 0.69). Statistically significant association was between opioids analgesia group and tramadol, non-opioids and group without analgesia (p ≤ 0.01). The need for strict guidelines for administration of opioids in children with severe burn injury, which ensures an adequate level of analgesia. Parenteral Tramadol can ensure only partial removal of pain. Unacceptable use of only non-narcotic analgesics or start transportation to hospital without analgesia.